Situation Report: Romania, 12 July 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Manescu Receives Yugoslav Ambassador Reaction to Czechoslovak Situation Czechoslovak Ambassador to Romania Presents Credentials New Minister of Electric Power Foreign Trade Bank Established Economic News Religious News